2009
DOI: 10.1080/23808985.2009.11679084
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Consumer Advertising Appeals to Cultural Values A Meta-Analytic Review of Effects on Persuasiveness and Ad Liking

Abstract: It is a truism that successful persuasive messages should be adapted to audi ence values. A substantial research literature-not previously systematically reviewed-has examined whether advertisements with appeals adapted to the audience's important cultural values (e.g., individualism for North Americans) are more persuasive and better liked than appeals that are unadapted to such values. A meta-analytic review of that research finds that adapted ads are only slightly more persuasive (mean r = .073, 67 cases) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 71 publications
0
56
0
4
Order By: Relevance
“…It is understood that advertising messages targeted at audiences from different parts of the world do not always travel, which increases the need for adapting messages across the globe instead of standardizing them (e.g., Agrawal, 1995;Hornikx & O'Keefe, 2009;La Ferle, Edwards, & Lee, 2008). It seems straightforward that, when communicating with their target audience in different cultures, companies want to clearly mention the benefits of their products in order to maximize their impact (see Wyer & Shrum, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that advertising messages targeted at audiences from different parts of the world do not always travel, which increases the need for adapting messages across the globe instead of standardizing them (e.g., Agrawal, 1995;Hornikx & O'Keefe, 2009;La Ferle, Edwards, & Lee, 2008). It seems straightforward that, when communicating with their target audience in different cultures, companies want to clearly mention the benefits of their products in order to maximize their impact (see Wyer & Shrum, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The significant effects found for attitude towards the letter and credibility of the organization, however, were rather large: r ϭ .17 for credibility of the organization, and r ϭ .28 for attitude towards the letter. These effect sizes are larger than the average effect size found in the meta-analysis of Hornikx and O'Keefe (2009) that summarizes empirical investigations on cultural value adaptation in advertisements.…”
Section: Conclusion and Discussionmentioning
confidence: 51%
“…As the interaction between world-view and appeal on persuasiveness was not significant, the adaptation effect cannot be empirically attributed to world-view (i. e., the difference in persuasiveness between the help-others and the help-self appeal was not stronger for participants with a strong care-orientation than for participants with a weaker care-orientation). It should be noted that a lack of a direct empirical explanation such as in the present study has been reported frequently in studies on cultural adaptation of value appeals (see Hornikx and O'Keefe, 2009). To what extent can the cultural adaptation effect found in the present study be explained by culture?…”
Section: Conclusion and Discussionmentioning
confidence: 74%
See 2 more Smart Citations